2021
DOI: 10.3390/su13063422
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Technologies and Recent Developments for Sustainable Smart Cycling

Abstract: Among the problems resulting from the continuous urbanization process, inefficient urban mobility and high pollution levels have been complex challenges that have demanded a lot of public investments and research efforts. Recently, some alternative transportation means have been leveraged as sustainable options for such challenges, which has brought bicycles to a more relevant setting. Besides the sometimes obvious benefits of adopting bikes for transportation, technologies around the Internet of Things (IoT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 154 publications
0
11
0
4
Order By: Relevance
“…This situation requires alternative approaches, such as for example, walking meetings, which has been reported to also lead to social benefits ( 161 ), as well as some recently proposed solutions with promising results, including intermittent upper body ergometry, an attractive option for those who prefer to remain in the seated position ( 162 ), and low-cost standing desks, which are made out of cardboard, are suitable for use in different locations such as at home, and can have an inexpensive and environment-friendly recycling process ( 163 , 164 ). Despite the challenges involved in implementing public policies that contemplate widespread access to PA promotion and sedentary behavior reduction initiatives, especially in low-income settings, localized comprehensive interventions have been recently implemented in many countries, including Canada and Brazil, and must be scaled up ( 60 , 101 , 146 , 165 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation requires alternative approaches, such as for example, walking meetings, which has been reported to also lead to social benefits ( 161 ), as well as some recently proposed solutions with promising results, including intermittent upper body ergometry, an attractive option for those who prefer to remain in the seated position ( 162 ), and low-cost standing desks, which are made out of cardboard, are suitable for use in different locations such as at home, and can have an inexpensive and environment-friendly recycling process ( 163 , 164 ). Despite the challenges involved in implementing public policies that contemplate widespread access to PA promotion and sedentary behavior reduction initiatives, especially in low-income settings, localized comprehensive interventions have been recently implemented in many countries, including Canada and Brazil, and must be scaled up ( 60 , 101 , 146 , 165 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is aligned with a global action plan on PA, highlighting the contributions of an increase in active recreation, sports, walking, and cycling to a sustainable and prosperous world ( 145 ). Reductions in traffic volumes and speeds, along with improving infrastructure to provide safe and welcoming spaces for active transportation, lead to a decrease in traffic accidents and pollution ( 146 ). Other incentives to active commuting, such as bike-sharing programs, reduce automobile use and decrease fossil fuel consumption, thereby contributing to the mitigation of climate change ( 69 ).…”
Section: Macro-environmental Dimensions Of Physical Activitymentioning
confidence: 99%
“…In a world where shared systems have been used for a long time, especially shared bicycles and more recently shared e-scooters, the use of technology to collect data that includes temporal and spatial patterns can help understand people's behavior and the impacts and limitations of these solutions to promote urban sustainability [32]. Besides, if all elements associated with urban mobility are connected and integrated, much better decisions can be taken on a real-time basis [33].…”
Section: Sustainable and Smart Mobilitymentioning
confidence: 99%
“…Sydney exhibited a surge in the willingness to cycle due to hygiene reasons and recreational exposure [24]. In addition, delivery services increased their reliance on cycling during this period [25].…”
Section: Physical and Mental Wellbeing Outcomesmentioning
confidence: 99%
“…Venter et al [126] incorporated pedestrian activities (running, hiking, and waking) to investigate the recreational use of urban green spaces during the COVID-19 partial lockdown in Oslo, Norway. Griffin et al [127] claimed that pedestrian studies are limited, while Oliveira et al [25] indicated that emerging micromobility and conventional non-motored vehicles (i.e., skateboards, scooters, and rollerblades) share common challenges and interests with conventional bikes. Cycling is suitable for journeys that are too long for walking and too short for driving [128].…”
Section: Non-cycling Modesmentioning
confidence: 99%